Three new species of Dinera Robineau-Desvoidy from China (Diptera: Tachinidae) - Zhang, Chun-Tian; Fu, Chao (Zootaxa, 2012)
Three species of the genus Dinera Robineau-Desvoidy (Diptera: Tachinidae) are described from China as new to science:D. borealis sp. nov., D. guangxiensis sp. nov. and D. nigrisquama sp. nov. Illustrations of the head and male terminalia are given as well as a modified key.